2020
DOI: 10.1037/ort0000447
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and impacts of intersectionality on obsessive-compulsive disorder symptoms across intensive treatment.

Abstract: Historically, intensive obsessive-compulsive and related disorder (OCRD) treatment settings have been underrepresentative in terms of patient race and ethnicity. The present study piloted a novel technique to measure multiple marginalized identities and assess their impact on obsessive-compulsive disorder (OCD) symptoms and treatment response across intensive residential treatment (IRT). Participants included 715 residents receiving IRT for OCRD. Measures included the Yale-Brown Obsessive-Compulsive Scale, Dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…These identities alone were associated with comparable or greater discriminatory trauma than non-specific intersectional identities. Nonetheless, clinicians should be aware that greater intersectionality is more likely to signal cumulative trauma, and it also can be an impediment to treatment, as has been seen with other disorders as well (eg, 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…These identities alone were associated with comparable or greater discriminatory trauma than non-specific intersectional identities. Nonetheless, clinicians should be aware that greater intersectionality is more likely to signal cumulative trauma, and it also can be an impediment to treatment, as has been seen with other disorders as well (eg, 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Race, ethnicity, gender, sexual orientation and ableism constitute some examples of identities that may be societally privileged or marginalized according to group membership. Wadsworth et al (2020) demonstrated that holding more marginalized identities increased OCD symptom severity in the contamination, harm and symmetry dimensions at baseline and discharge for OCD patients. Furthermore, having more marginalized identities was related to increased obsessive beliefs about responsibility/threat over-estimation and perfectionism/certainty at both time points.…”
Section: The Connection Between Discrimination and Ocdmentioning
confidence: 95%
“…Having several marginalized identities can compound the effects of discrimination on OCD phenomenology. Intersectionality refers to belonging to two or more communities that have been historically marginalized (Wadsworth et al, 2020). Race, ethnicity, gender, sexual orientation and ableism constitute some examples of identities that may be societally privileged or marginalized according to group membership.…”
Section: The Connection Between Discrimination and Ocdmentioning
confidence: 99%
“…Across numerous studies, experiences of racial discrimination have been found to predict and exacerbate OCD symptoms and access to care [e.g., 12 ]. For instance, Wadsworth and colleagues [ 13 ] examined having multiple marginalized identities with OCD symptoms and intensive residential treatment response and found that those with more marginalized identities had an increased severity of fear of contamination concerns. Further, possessing multiple marginalized identities was associated with heightened OCD symptoms at both admission and discharge from the treatment program.…”
Section: Obsessive–compulsive Disordermentioning
confidence: 99%